Indented Pixel Tree Browser for Exploring Huge Hierarchies - Burch, Michael; Schmauder, Hansjörg; Weiskopf, Daniel (Advances in Visual Computing: Proceedings of the International Symposium on Visual Computing 2011, 2011)
In this paper we introduce the Indented Pixel Tree Browser -- an interactive tool for exploring, annotating, and comparing huge hierarchical structures on different levels of granularity. We exploit the indented visual metaphor to map tree structures to one-dimensional zigzag curves to primarily achieve an overview representation for the entire hierarchy. We focus on space-efficiency and simultaneous uncovering of tree-specific phenomena. Each displayed plot can be filtered for substructures that are mapped to a larger space and hence, unhide more fine-granular substructures that are hidden in the compressed overview. By representing tree structures side-by-side, the viewer can easily compare them visually and detect similar patterns and also anomalies. In our approach, we follow the information seeking mantra: overview first, zoom and filter, then details-on-demand. More interactive features such as expanding and collapsing of nodes, applying different color codings, or distorting the tree horizontally as well as vertically support a viewer when exploring huge hierarchical data sets. The usefulness of our interactive browsing tool is demonstrated in a case study for the NCBI taxonomy that contains 324,276 species and organisms that are hierarchically organized.